PENGAJUAN KREDIT SEPEDA MOTOR MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS (STUDI KASUS SHOWROOM YOYO) - Nuri Latifa Efrata; Jijon Raphita Sagala (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
The company sets policies in granting credit, among others, sets the Standard for accepting or rejecting credit risk, namely determining who has the right to receive credit that has fulfilled the five C requirements, what is the character of the customer, capacity to repay credit, the ability of capital owned by the customer (capital), collateral owned by the customer to bear credit risk (collateral) and the customer's financial condition (condition). Decisions are reached after consideration is made by choosing one possible choice. Decisions are categorized as feasible and not feasible. The criteria set by the company in applying for credit are personality, advances, abilities, guarantees, conditions. With the AHP method, from the criteria determined the intensity of the importance / priority scale on the criteria. After doing the calculation process, the credit decision was obtained from the ranking of the AHP method: 0.258652 (feasible), 0.2569579 (feasible), 0.2445319 (not feasible), 0.2398582 (not feasible).